The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages 3. Food. The necessity to make food go round in war-time has produced not only rationing and price-control for basic foods, but also the British Restaurants, and has stimulated the growth of factory canteens. Too often these amenities are regarded as a temporary expedient, which can be dropped after the war. But they have opened out to many housewives, and to workers living alone, the prospect of a better way of life — for the housewife freedom from the endless drudgery of buying and preparing food at home day after day, and for the lonely worker a welcome relief from the gas-ring meal and sandwich lunch. The restaurant has never been before regarded as a social service, but as the preserve of private enterprise, and any alteration in this state of affairs will no doubt be strenuously opposed by "vested interests." But there is a very strong case for their inclusion in a social service scheme, for apart from their value in helping to distribute food fairly, and in feeding those who might otherwise be inadequately fed, they have a value as social centres, and also in their effect on domestic life. The woman who knows that she and her family can have a meal out when they feel like it has a different outlook from the one who can see nothing in front of her but an endless vista of meals to be bought and cooked. British restaurants have in some places been used as social 12 15X/2/464/1